Rancang Bangun Model Dampak Perubahan Penggunaan Lahan dalam Pembangunan HTI Pulp (Modeling Land Use Change Impacts around Developed HTI Pulp Concession Area) - Donny Iskandar; Hadi S Alikodra; Hartrisari H Hardjomidjojo; Bambang Pramudya N (Institut Pertanian Bogor (IPB University), 2006)
This research aim to establish a land use change model purposed to figure a spatial ecological equilibrium out from the land used activities. The analyzing of these land use change impacts were adopted from modeling methods, based from system thinking approach. Although the analytical constructions dominated by social sciences, all methodologies were drawn from more than one field of discipline to analyze the nature-society-economy relationships. These interdisciplinary orientation combining concepts has some advantages in recognizing most complex variables in the real world than another functional approaches. The model has verified to validate in villages around the HTI concession area of Jambi Province which is managed by PT Wirakarya Sakti (WKS), and resulted some behavior patterns of land use changed that showed in descriptions as a whole. At last, sensitivity analysis of this model - like a game - has developed the “what if” input variables to predict situation of the future, and has resulted some options of scenario as decision support to the policy system framework.Keywords: Ecologycal equilibrium, HTI pulp concession area, land use change, modeling, system thinking approach, decision support system, Jambi.